การใช้กระดาษพิมพ์เขียนใช้แล้วและกากกระดาษฉลากบรรจุภัณฑ์ในวัสดุเชิงประกอบเปเปอร์ครีต - วิภาวี เข็มเฉลิม (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Papercrete is a construction material similar to concrete. It is fairly strong lightweight, and low cost. It is considered as one of the environmentally friendly building materials. Papercrete mixes basically consist of Portland cement, sand and pulps derived from recycled papers. This research described a viability of using printing/writing and label paper wastes in papercrete composites. To make a papercrete, three steps were undergone. Firstly, both types of paper were soaked in alkali solution to soften paper and turn them to fibers. Forming the handsheets to see how different types of fiber could affect papercrete properties was carried out. Secondly the ratio of cement to sand was investigated then it was found that a ratio of cement to sand of 0.75:1 with superplasticizer 5 wt% of them and the water/cement ratio of 0.35 made highest compressive strength with low fluctuation. Thirdly, three mixes with 10, 20 and 30wt% of fibers were prepared. They were cured for 1, 3, 7, and 14 days in a damp, ambient conditioner. The experimental results showed that a papercrete with used printing/writing fibers had low density and compressive strength but owned higher percent volume change compared with a normal concrete. With 10 wt% fibers, the obtained papercrete had highest compressive strength. An increase in compressive strength depended on curing times. The label-containing papercrete yielded highest compressive strength of 3.55 MPa when cured for 14 days. Meanwhile, those with printing/writing fibers did not follow this trend due to their different hydrophobicity. So, papercretes with label waste seemed to be more applicable to use as a lightweight, indoor construction material.